INTERFERENCE REDUCTION USING CLUSTERING ALGORITHM IN VANET - Saravanan, H.; Bhavani, T.; Priyashanthini,; S, Sanju; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
Vehicular ad hoc networks (VANETs) are a subclass of MANETs that is expected to have a key role in the intelligent transportation systems of the future. The mobile nodes can move around, and the network would automatically reconfigure itself to allow connectivity. VANETs provide vehicle-to-vehicle and vehicle-to-roadside communication in order to support safety and comfort applications. Despite being a subclass of MANETs, VANETs fundamentally have different behavior. This paper presents a scheme consisting of a media access control protocol and a clustering algorithm designed to reduce interferences in VANETs. Our scheme, which is intended for safety applications in highway environments, employs dynamic multihop clustering, allows better utilization of network resources and improves network performance.